2016
DOI: 10.1177/1553350616660630
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase From Vibrio alginolyticus Cultures

Abstract: Purpose The purpose of this study is to examine the activity of collagenase from cultures of Vibrio alginolyticus as in vitro as in biological samples and to evaluate clinical perspectives of this product about the treatment of fibroproliferative diseases like Dupuytren's contracture. Methods The experimental part of the study has been divided in 2 stages. In the first stage, the collagenase has been produced in laboratory, assessing its purity, verifying the in vitro degradation of collagen by the enzyme and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Although some may be considered pathogens to aquatic animals and humans [88], V. alginolyticus strains are recognized to be typical coral symbiotic bacteria [60], which are also frequently present in healthy fish, shrimps, and mollusks [89] and whose biotechnological potential has been used for collagenase production in the clinic [90]. With regard to the QSI potential of V. alginolyticus , although Wang et al [91] have reported that the diketopiperazine cyclo (Leu-Pro) produced by a strain of this species isolated from sea anemones is capable of inhibiting mussel fouling, its QSI capacity was not tested.…”
Section: Discussionmentioning
confidence: 99%
“…Although some may be considered pathogens to aquatic animals and humans [88], V. alginolyticus strains are recognized to be typical coral symbiotic bacteria [60], which are also frequently present in healthy fish, shrimps, and mollusks [89] and whose biotechnological potential has been used for collagenase production in the clinic [90]. With regard to the QSI potential of V. alginolyticus , although Wang et al [91] have reported that the diketopiperazine cyclo (Leu-Pro) produced by a strain of this species isolated from sea anemones is capable of inhibiting mussel fouling, its QSI capacity was not tested.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its low metabolic activity against fibronectin and decorin, the primary utility of Vibrio collagenases depends on their capability to perform the careful eradication of necrotic tissue [ 44 , 50 ] with only minor damage to the periwound healthy tissues [ 51 , 52 ]. V. collagenase has been established to be valuable and adequate as a debriding instrument and is being recommended for pharmaceutical use [ 53 ]. The value and accordance of collagenase have been a recurring theme in the literature between batches and manufacturers [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…The secreted collagenase from V. alginolyticus is being successfully applied for pharmaceutical uses [30] and references therein] that exhibits limited non-specific proteolytic activity, which reduces side effects due to digestion of healthy tissues [31]. Therefore, such enzyme, which is industrially produced by autologous expression, has proven to be useful and effective as debriding agent for medical uses (i.e., ointments and other devices).…”
Section: Introductionmentioning
confidence: 99%